Continuous carbon fiber reinforced resin-based composite material and preparation method thereof
By adding an inorganic nanoparticle electrospinning film between the prepreg belts of the continuous carbon fiber reinforced resin-based composite material, the problem of insufficient interlayer shear strength is solved, and the interlayer bonding and mechanical properties of the material are significantly improved.
Patent Information
- Application Number
- CN202311033979.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-17
- Publication Date
- 2025-02-21
AI Technical Summary
The existing continuous carbon fiber reinforced resin-based composite materials have shortcomings in interlayer shear strength, resulting in interlayer layering failure and reducing the stiffness and strength of the material.
The thermoplastic resin electrospinning film was added between the prepreg bands of the continuous carbon fiber reinforced resin-based composite material, and inorganic nanoparticles with a mass content of 0.05%-5% are introduced into the electrospinning film to improve the micromechanical properties and layers of the interface Interbonding performance.
By introducing an electrospinning film of inorganic nanoparticles, the interlayer bonding and mechanical properties of the continuous carbon fiber reinforced resin-based composite material are significantly improved, the agglomeration of inorganic nanoparticles is avoided, and the uniform and stable performance of the material is improved.
Abstract
Description
Technical Field
[0001] The invention relates to a composite material, in particular to a continuous carbon fiber reinforced resin-based composite material and a preparation method thereof. Background Art
[0002] Continuous carbon fiber reinforced resin-based composite materials are carbon fiber reinforced composite materials in which carbon fibers are dispersed in a thermoplastic resin matrix or a thermosetting resin matrix. They have the performance characteristics of both carbon fiber and resin, and have the characteristics of high specific strength, high specific modulus, light weight, wear resistance, dimensional stability and corrosion resistance. They are widely used in wind power generation, new automobiles, aerospace, instruments and equipment, sporting goods, building materials and other fields. With the advancement of related technologies, the demand for them is also increasing year by year. Accordingly, the requirements for the performance characteristics of continuous carbon fiber reinforced resin-based composite materials are also higher, and the product performance of continuous carbon fiber reinforced resin-based composite materials used in different application scenarios is also more targeted.
[0003] The preparation process of continuous carbon fiber reinforced resin-based composite materials can be roughly divided into two different process stages: the first stage is the prepreg process stage, in which the resin is compounded with carbon fiber in a solution state, a molten state, a powder state, etc. to form a mixed / impregnated semi-finished product, usually in the form of a prepreg tape; the second stage is the molding process stage, in which multiple prepreg tapes are used to remove the gas contained in the material at a certain temperature and pressure, further complete the impregnation of the resin and carbon fiber, remove the voids in the material, and consolidate under pressure and (or) temperature to form a dense structure to obtain the final continuous carbon fiber reinforced thermoplastic resin-based composite material.
[0004] One of the important technical indicators of the existing continuous carbon fiber reinforced resin-based composite materials is the interlaminar shear strength (ILSS). The interlaminar shear strength of the composite material refers to the stress generated inside the material as a resistance when the adjacent layers of the fiber material product are relatively displaced after lamination (i.e. the second stage of the above process, the molding process stage). The existence of interlaminar stress can easily lead to interlaminar damage of the composite material, and interlaminar delamination will seriously reduce the stiffness and strength of the composite material. Therefore, interlaminar problems such as interlaminar stress and interlaminar shear strength are issues that need to be considered in the design and preparation of continuous carbon fiber reinforced resin-based composite materials.
[0005] Invention patent CN201710849943.5 discloses a method for preparing a compatibilizer for carbon fiber reinforced poly(phenylene ether sulfone) blended resin-based composite materials, invention patent CN201410268521.5 discloses a method for preparing continuous carbon fiber reinforced poly(phenylene ether nitrile) resin-based composite materials, invention patent ZL200610134662.3 discloses an interface modification method for continuous fiber reinforced poly(phenylene ether sulfone ketone) composite materials, etc. Invention patent CN110435185A discloses a method and device for preparing a carbon fiber reinforced thermoplastic resin-based composite material, wherein the carbon fiber is modified with hydroxyl groups to improve the carbon fiber, and a carbon fiber reinforced thermoplastic resin-based composite material is obtained after drying, compression molding and other processes, and the method improves the interface bonding strength and related properties between the carbon fiber and the resin matrix. Summary of the invention
[0006] In view of the deficiencies in the prior art, the present invention provides a continuous carbon fiber reinforced resin-based composite material and a preparation method thereof, which can effectively enhance the interlayer bonding performance and mechanical properties of the continuous carbon fiber reinforced resin-based composite material.
[0007] According to a first aspect of the present invention, the present invention provides a method for preparing a continuous carbon fiber reinforced resin-based composite material.
[0008] Specifically, a method for preparing a continuous carbon fiber reinforced resin-based composite material of the present invention comprises the following steps: S1: Preparation of continuous carbon fiber reinforced resin matrix composite prepreg tape; S2: adding a thermoplastic resin electrospinning membrane between the layers of the continuous carbon fiber reinforced resin-based composite material prepreg tape obtained in step S1; S3: Compression molding the multi-layer continuous carbon fiber reinforced resin-based composite material prepreg tape with thermoplastic resin electrospinning membrane added between the layers obtained in step S2 to obtain a continuous carbon fiber reinforced resin-based composite material.
[0009] Furthermore, the process of preparing the continuous carbon fiber reinforced resin matrix composite material prepreg tape in step S1 can adopt conventional operations in the art. Typical methods for preparing the continuous carbon fiber reinforced resin matrix composite material prepreg tape include solution impregnation method and melt impregnation method.
[0010] Further, a typical method for preparing a continuous carbon fiber reinforced resin-based composite material prepreg tape by a solution impregnation method comprises the following steps: S11: dissolving the resin in a solvent to form a resin glue solution; S12: After fully impregnating the continuous carbon fiber in the resin glue, drying is performed to obtain a continuous carbon fiber reinforced resin-based composite material prepreg tape.
[0011] Further, a typical method for preparing a continuous carbon fiber reinforced resin-based composite material prepreg tape by melt infusion comprises the following steps: S11: melting the resin matrix at high temperature to form a flowing resin liquid; S12: After the continuous carbon fiber is fully impregnated in the resin flowing liquid, it is cooled to obtain a continuous carbon fiber reinforced resin matrix composite material prepreg tape.
[0012] Further, the thermoplastic resin electrospun membrane described in step S2 is selected from at least one of an electrospun polyurethane film, an electrospun polyvinylidene fluoride film, an electrospun polyaryletherketone film, an electrospun polyarylethersulfone resin film, an electrospun polysulfone film, an electrospun polyethersulfone film, an electrospun polyphenylene sulfone film, an electrospun polyphenylene sulfone film, an electrospun polyetherimide film, and an electrospun polypropylene film.
[0013] Furthermore, the resin matrix used in the continuous carbon fiber reinforced resin-based composite material prepreg tape described in step S1 includes, but is not limited to, at least one of copolyarylethersulfone resin, polysulfone, polyethersulfone, polyphenylenesulfone, polyphenylenesulfone, polyetherimide, polyaryletherketone, polyamideimide, polypropylene, and polyamide. Preferably, the resin matrix in step S1 is the same as the resin matrix of the electrospinning membrane in step S2 or has similar compatibility.
[0014] Further, the thermoplastic resin electrospinning membrane described in step S2 contains inorganic nanoparticles with a mass content of 0.05%-5%. The average particle size of the inorganic nanoparticles is generally 50-500 nm. The inorganic nanoparticles are a mixture of one or more of nano metal oxides, nano metal carbonates, nano metal hydroxides, nano metal sulfates, nano metal nitrates, nano silicon dioxide, nano montmorillonite, and nano kaolin. The preferred inorganic nanoparticles are selected from nano calcium carbonate and / or nano montmorillonite. The inventors of the present application unexpectedly discovered through research that the introduction of inorganic nanoparticles can further improve the interface micromechanical properties between the thermoplastic resin electrospinning membrane and the continuous carbon fiber reinforced resin-based composite material prepreg, thereby improving the interlayer bonding performance between two adjacent layers of continuous carbon fiber reinforced resin-based composite material prepreg, and thereby improving the interlayer mechanical properties of the continuous carbon fiber reinforced resin-based composite material.
[0015] Furthermore, the inorganic nanoparticles are preferably modified calcium carbonate. The modified calcium carbonate is obtained by treating the surface of calcium carbonate with sodium stearate. The thermal weight loss temperature of the obtained modified calcium carbonate inorganic nanoparticles is above 600°C, which fully meets the high temperature process conditions during compression molding in S3.
[0016] Furthermore, between step S1 and step S2, the method further includes: step S4, wherein the thermoplastic resin electrospinning membrane containing inorganic nanoparticles is prepared by the following method: S41: preparing an electrospinning solution, adding a thermoplastic resin and inorganic nanoparticles into a solvent to prepare an electrospinning solution, and uniformly dispersing the electrospinning solution to obtain an electrospinning solution containing inorganic nanoparticles; the concentration of the electrospinning solution is 5%-30%; S42: loading the electrospinning solution containing inorganic nanoparticles into the injection needle of the electrospinning device, installing the device on the electrospinning device, and preparing an electrospinning membrane containing inorganic nanoparticles by an electrospinning process, wherein the voltage is 10-20 kV and the electrospinning solution jet flow rate is 60-200 mL / min; S43: The electrospinning membrane containing inorganic nanoparticles obtained in step S42 is cleaned and then dried.
[0017] Preferably, the electrospinning membrane containing inorganic nanoparticles in step S4 is prepared by the following method: S41: preparing an electrospinning solution, adding a thermoplastic resin into a solvent to prepare an electrospinning solution, wherein the concentration of the electrospinning solution is 5%-30%; S42: loading the electrospinning solution into an injection needle tube of the electrospinning device, installing the device on the electrospinning device, and ejecting the electrospinning solution from the injection device through a spinneret to form an electrospinning solution jet; ejecting inorganic nanoparticles at a constant speed into the electrospinning solution jet on the side of the electrospinning solution jet to obtain an electrospinning solution jet containing inorganic nanoparticles; S43: The electrospinning liquid jet containing inorganic nanoparticles is sprayed onto a collecting plate to form an electrospinning membrane containing inorganic nanoparticles.
[0018] Furthermore, the composition and preparation of the electrospinning solution in step S41 are common knowledge known to those skilled in the art.
[0019] Further, the process conditions of electrospinning in step S42 are common knowledge in the art. For example, typical electrospinning conditions use a high voltage electric field of 10-20 kV, an electrospinning solution flow rate of 60-200 mL / min, and after the electrospinning solution jet is sprayed onto the collecting plate, a film shape is formed on the mold surface. The inorganic nanoparticle emission rate is generally 0.1-10 mg / min.
[0020] The inventors of the present application have discovered that by isotropically emitting inorganic nanoparticles into the electrospinning liquid jet, it is possible to ensure that the inorganic nanoparticles in the electrospinning membrane obtained are more evenly and stably dispersed, without agglomeration and other uneven phenomena. The uniformity and stability of the electrospinning membrane of inorganic nanoparticles can further improve the interlaminar mechanical properties and performance uniformity and stability of the final carbon fiber reinforced resin-based composite material.
[0021] Furthermore, the compression molding described in step S3 adopts conventional operations in the art. The multi-layer continuous carbon fiber reinforced resin prepreg tapes with thermoplastic resin electrospinning membranes added between the layers obtained in step S2 are neatly stacked, placed in a mold, molded for a certain time at a specific temperature and pressure, and cooled naturally to room temperature while maintaining the pressure. After demolding, a continuous carbon fiber reinforced resin-based composite material is prepared. The molding temperature is 160°C-350°C, the pressure is 5-10MPa, and the molding time is generally 0.1-1h.
[0022] According to a second aspect of the present invention, the present invention also provides a continuous carbon fiber reinforced resin-based composite material, which is prepared by the method described above.
[0023] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention prepares a continuous carbon fiber reinforced resin-based composite material by adding a thermoplastic resin electrospinning membrane between the layers of the continuous carbon fiber reinforced resin-based composite material prepreg tape, and utilizes the pores in the thermoplastic resin electrospinning membrane to facilitate the flow and bonding of the interlayer resin, which is beneficial to improving the interlayer bonding and mechanical properties of the composite laminate. The thermoplastic resin electrospinning membrane containing inorganic nanoparticles achieves effective dispersion of inorganic nanoparticles between the layers of the continuous carbon fiber reinforced resin-based composite material prepreg tape, avoiding the agglomeration of inorganic nanoparticles and reducing the mechanical properties of the continuous carbon fiber reinforced resin-based composite material product; the preparation process of the present invention does not change the equipment for preparing the continuous carbon fiber reinforced resin-based composite material in the prior art, is easy to implement, and is economically reasonable.
[0024] 2. In the present invention, inorganic nanoparticles are preferably introduced in the process of preparing an electrospinning membrane containing inorganic nanoparticles, that is, inorganic nanoparticles are uniformly emitted and sprayed into the electrospinning liquid jet to obtain an electrospinning liquid jet containing inorganic nanoparticles, and the electrospinning liquid jet containing inorganic nanoparticles is sprayed onto a collecting plate to form an electrospinning membrane containing inorganic nanoparticles. This process can ensure that the inorganic nanoparticles in the obtained electrospinning membrane are uniformly and stably dispersed, and there will be no uneven phenomena such as agglomeration. The uniformity and stability of the electrospinning membrane of inorganic nanoparticles can further improve the interlaminar mechanical properties and the uniformity and stability of the performance of the final carbon fiber reinforced resin-based composite material. Implementation
[0025] The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention.
[0026] In the examples and comparative examples, the average particle size of the nano-calcium carbonate particles is 100 nm, and the average particle size of the nano-titanium dioxide particles is 200 nm.
[0027] The tensile strength test was performed according to ATSM D3039-2007 standard, and the shear strength test was performed according to ATSM D2344-2016 standard. Example 1
[0028] The method of this embodiment includes the following steps: S1: Preparation of continuous carbon fiber reinforced resin matrix composite prepreg tape: S11, dissolving the poly(arylethersulfone) copolymer resin with a phthalazine structure in an N-methylpyrrolidone solvent to obtain a resin glue solution; in the resin glue solution of the present embodiment, the mass percentage of the poly(arylethersulfone) copolymer resin with a phthalazine structure is 16wt%; the structure of the poly(arylethersulfone) copolymer resin with a phthalazine structure is: , Where x=160, y=40.
[0029] S12, after fully impregnating the continuous carbon fiber in the resin glue solution of step S11, drying at 80°C under normal pressure for 1 hour to obtain a continuous carbon fiber reinforced naphthalene biphenyl structure co-polyarylethersulfone resin-based composite material prepreg tape; in the obtained continuous carbon fiber reinforced naphthalene biphenyl structure co-polyarylethersulfone resin-based composite material prepreg tape, the mass contents of the continuous carbon fiber and the naphthalene biphenyl structure co-polyarylethersulfone resin are: 55% of the continuous carbon fiber and 45% of the naphthalene biphenyl structure co-polyarylethersulfone resin; S2: cutting the continuous carbon fiber reinforced copolyarylethersulfone prepreg tape prepared in step S1 into a size consistent with the size of the mold, laying 16 pieces of the continuous carbon fiber reinforced copolyarylethersulfone prepreg tapes in the mold according to the requirements of the mechanical properties and thickness of the continuous carbon fiber reinforced resin-based composite material, and laying 15 pieces of polyarylethersulfone electrospinning membranes between the layers of the continuous carbon fiber reinforced naphthalene biphenyl structure copolyarylethersulfone resin-based composite material prepreg tape prepared in step S1; Among them, the polyarylethersulfone electrospinning membrane is prepared by the existing technology, and the preparation process of the polyarylethersulfone electrospinning membrane is as follows: prepare a polyarylethersulfone electrospinning solution with a mass fraction of 20%; use a syringe to extract the polyarylethersulfone electrospinning solution, and spin it on an electrospinning machine with an injection flow rate of 80mL / min and a voltage of 16kV to prepare the polyarylethersulfone electrospinning membrane by the electrospinning process.
[0030] S3: The multi-layer continuous carbon fiber reinforced poly(phenylene ether sulfone) structure co-poly(phenylene ether sulfone) resin-based composite material prepreg with poly(phenylene ether sulfone) electrospinning membrane added between the layers obtained in step S2 is compression molded, placed in a hot press and molded, heated to 340°C, 7MPa, maintained at a pressure of 20 minutes, and demolded after decompression and cooling to obtain a 2mm thick continuous carbon fiber reinforced poly(phenylene ether sulfone) structure co-poly(phenylene ether sulfone) resin-based composite material.
[0031] Example 2 (composite material containing electrospun membrane containing inorganic nanoparticles added by conventional method) The method for preparing a continuous carbon fiber reinforced poly(phenylene ether sulfone) resin-based composite material of Example 2, steps S1, S2, and S3 are consistent with those of Example 1, but further includes between step S1 and step S2: step S4, preparing a thermoplastic resin electrospinning membrane containing inorganic nanoparticles by conventional means. Specifically, S41: preparing an electrospinning solution containing calcium carbonate nanoparticles, adding polyarylethersulfone resin and calcium carbonate nanoparticles into a solvent to prepare an electrospinning solution, and uniformly dispersing the electrospinning solution to obtain an electrospinning solution containing calcium carbonate nanoparticles; the concentration of the polyarylethersulfone electrospinning solution is 20%, adding 0.5% by mass of calcium carbonate nanoparticles into the polyarylethersulfone spinning solution, and uniformly distributing the calcium carbonate nanoparticles in the polyarylethersulfone spinning solution by magnetic stirring to obtain a polyarylethersulfone electrospinning solution containing calcium carbonate nanoparticles; S42: The polyarylethersulfone electrospinning solution containing calcium carbonate nanoparticles is loaded into the injection needle of the electrospinning device, and the device is installed on the electrospinning device. The electrospinning solution injection flow rate is 80mL / min, the voltage is 16kV, and the polyarylethersulfone electrospinning membrane containing calcium carbonate nanoparticles is prepared by the electrospinning process.
[0032] S43: washing the polyarylethersulfone electrospinning membrane containing calcium carbonate nanoparticles obtained in step S42 and then drying it.
[0033] Example 3 (Composite material containing electrospun membrane containing inorganic nanoparticles) The method steps for preparing a continuous carbon fiber reinforced naphthalene biphenyl structure co-polyarylethersulfone resin-based composite material in Example 3 are consistent with steps S1, S2, and S3 in Example 2, but step S4 between step S1 and step S2 is different. The preparation process of the polyarylethersulfone electrospinning membrane containing calcium carbonate nanoparticles in step S4 of this embodiment is an innovative method. Specifically, the electrospinning membrane containing inorganic nanoparticles in step S4 is prepared by the following method: S41: preparing an electrospinning solution, adding a thermoplastic resin into a solvent to prepare an electrospinning solution, wherein the concentration of the electrospinning solution is 20%, and placing the electrospinning solution in a syringe of an electrospinning device; S42: loading the polyarylethersulfone electrospinning solution into the injection needle of the electrospinning device, installing the device on the electrospinning device, and ejecting the polyarylethersulfone electrospinning solution from the injection device through the spinneret to form an electrospinning solution jet, with an ejection flow rate of 80 mL / min and a voltage of 16 kV; ejecting calcium carbonate nanoparticles at a constant speed from the side of the polyarylethersulfone electrospinning solution jet into the polyarylethersulfone electrospinning solution jet, with an ejection speed of the calcium carbonate nanoparticles of 0.2 mg / min, to obtain a polyarylethersulfone electrospinning solution jet containing calcium carbonate nanoparticles; S43: The electrospinning liquid jet containing calcium carbonate nanoparticles is sprayed onto a collecting plate to form a polyarylethersulfone electrospinning membrane containing calcium carbonate nanoparticles.
[0034] Comparative Example 1 (composite material without adding electrospinning membrane) In order to further compare the mechanical properties of the continuous carbon fiber reinforced poly(phenylene) structure co-poly(arylether sulfone) resin-based composite materials prepared in Examples 1, 2 and 3 with the composite materials prepared by the prior art, 16 pieces of continuous carbon fiber reinforced co-poly(arylether sulfone) resin prepreg tapes prepared in step S1 of Example 1 were neatly stacked in a mold, the mold was placed in a hot press and the temperature was raised to 340°C, the pressure was maintained at 7 MPa for 20 minutes, the pressure was released and the mold was demolded after cooling to obtain a continuous carbon fiber reinforced co-poly(arylether sulfone) resin composite material with a thickness of about 2 mm, which was used as Comparative Example 1 for Examples 1, 2 and 3.
[0035] The mechanical properties of the continuous carbon fiber reinforced naphthalene biphenyl structure co-poly(arylethersulfone) resin-based composite materials of Example 1, Example 2, Example 3 and Comparative Example 1 are listed in Table 1.
[0036] Table 1 product Tensile strength (MPa) Tensile modulus (GPa) Interlaminar shear strength (MPa) Example 1 1900 101 82 Example 2 1980 105 84 Example 3 2050 106 85 Comparative Example 1 1800 94 80 By comparing Example 1, Example 2, Example 3 and Comparative Example 1, it can be seen that the present invention has the following beneficial effects: With the poly(phenylene)-copolyethersulfone) resin having a naphthalene biphenyl structure as the matrix and the continuous carbon fiber as the reinforcement, the continuous carbon fiber reinforced poly(phenylene)-copolyethersulfone) resin-based composite material prepreg tape is added with an electrospinning membrane between the layers to prepare a continuous carbon fiber reinforced poly(phenylene)-copolyethersulfone) thermoplastic resin-based composite material, which can improve the mechanical properties of the continuous carbon fiber reinforced resin-based composite material. Further, the electrospinning membrane containing inorganic nanoparticles can further play the role of the electrospinning membrane. Due to the presence of inorganic nanoparticles, the adhesion between the prepreg tapes of the poly(phenylene)-copolyethersulfone) resin-based composite material is improved, thereby improving the mechanical properties. In particular, the preparation process of the electrospinning membrane containing inorganic nanoparticles of calcium carbonate in Example 3 can promote the effective dispersion of inorganic nanoparticles, and the pores in the electrospinning composite membrane are conducive to the flow and bonding of the interlayer resin, which is beneficial to improving the interlayer mechanical properties of the composite laminate, and providing a continuous carbon fiber reinforced poly(phenylene)-copolyethersulfone) resin-based composite material with excellent mechanical properties. By adding a high-performance thermoplastic resin electrospun composite membrane containing inorganic nanoparticles between layers, the dispersion of inorganic nanoparticles (calcium carbonate nanoparticles) between layers can be promoted, and the pores in the electrospun composite membrane are conducive to the flow and bonding of the interlayer resin, which is conducive to achieving interlayer reinforcement of the continuous carbon fiber reinforced copolymer polyarylethersulfone resin-based composite material. The continuous carbon fiber reinforced copolymer polyarylethersulfone resin-based composite material of this embodiment can be applied to wind power, petrochemical, automobile, rail transportation and other fields, and has broad application prospects.
[0037] Example 4 (adding ordinary electrospinning membrane between layers) The method for preparing the continuous carbon fiber reinforced resin composite material prepared in this embodiment 4 comprises the following steps: S1: Preparation of continuous carbon fiber reinforced polypropylene composite prepreg tape: S11, dissolving polypropylene resin in N-methylpyrrolidone solvent to obtain polypropylene resin glue solution, in which the mass percentage of polypropylene is 24wt%.
[0038] S12, after fully impregnating the continuous carbon fiber in the polypropylene resin glue of step S11, drying at 90°C under normal pressure for 1 hour to obtain a continuous carbon fiber reinforced polypropylene-based composite material prepreg tape; wherein the continuous carbon fiber is 48K T300 polyacrylonitrile-based carbon fiber; in the obtained continuous carbon fiber reinforced polypropylene-based composite material prepreg tape, the mass contents of the continuous carbon fiber and the polypropylene resin are: 50% of the continuous carbon fiber and 50% of the polypropylene resin; S2: adding a thermoplastic resin electrospinning membrane between layers of the continuous carbon fiber reinforced resin-based composite material prepreg tape, cutting the continuous carbon fiber reinforced polypropylene-based composite material prepreg tape prepared in step S1 into a size consistent with the size of the mold, laying 12 pieces of the continuous carbon fiber reinforced polypropylene composite material prepreg tape in the mold according to the requirements of the mechanical properties and thickness of the continuous carbon fiber reinforced resin-based composite material, and laying a total of 11 pieces of polypropylene electrospinning membrane between adjacent layers of the continuous carbon fiber reinforced polypropylene-based composite material prepreg tape prepared in step S1; The polypropylene electrospinning membrane is prepared by using the existing technology, and the specific preparation process is as follows: preparing a polypropylene electrospinning solution with a mass fraction of 17%; extracting the polypropylene electrospinning solution by using a syringe, spinning on an electrospinning machine, with an injection flow rate of 120 mL / min and a voltage of 20 kV, and preparing a polypropylene electrospinning membrane by an electrospinning process; S3: The multi-layer continuous carbon fiber reinforced polypropylene-based composite material prepreg with polypropylene electrospinning membrane added between the layers obtained in step S2 is compression molded, placed in a hot press and molded, heated to 240°C, 10MPa, maintained at a pressure of 10 minutes, and demolded after decompression and cooling to obtain a 1.6 mm thick continuous carbon fiber reinforced polypropylene-based composite material.
[0039] Example 5 (Electrospinning membrane with conventional inorganic nanoparticles added between layers) The method for preparing continuous carbon fiber reinforced polypropylene-based composite materials in this embodiment 5 is consistent with the steps S1, S2, and S3 of embodiment 4, but further includes between step S1 and step S2: step S4, preparing a thermoplastic resin electrospinning membrane containing inorganic nanoparticles by conventional means. Specifically, S41: preparing a polypropylene electrospinning solution containing titanium dioxide nanoparticles, adding polypropylene and titanium dioxide nanoparticles to a solvent to prepare an electrospinning solution, and uniformly dispersing the electrospinning solution to obtain an electrospinning solution containing titanium dioxide nanoparticles. Specifically, the concentration of the polypropylene electrospinning solution is 17%, and titanium dioxide nanoparticles with a mass fraction of 0.6% are added to the polyarylethersulfone spinning solution, and the titanium dioxide nanoparticles are uniformly distributed in the polypropylene electrospinning solution by magnetic stirring to obtain a polypropylene electrospinning solution containing titanium dioxide nanoparticles; S42: The polypropylene electrospinning solution containing titanium dioxide nanoparticles is loaded into the injection needle of the electrospinning device, and installed on the electrospinning device. The electrospinning solution injection flow rate is 120 mL / min, the voltage is 20 kV, and the polypropylene electrospinning membrane containing titanium dioxide nanoparticles is prepared by the electrospinning process.
[0040] S43: The polypropylene electrospinning membrane containing titanium dioxide nanoparticles obtained in step S42 is cleaned and then dried.
[0041] Example 6 The method steps for preparing continuous carbon fiber reinforced polypropylene-based composite materials in this embodiment 6 are consistent with steps S1, S2, and S3 in embodiment 5, but step S4 between step S1 and step S2 is different. The preparation process of polypropylene electrospinning membrane containing titanium dioxide nanoparticles in step S4 of this embodiment is an innovative method. Specifically, the electrospinning membrane containing inorganic nanoparticles in step S4 is prepared by the following method: S41: preparing an electrospinning solution, adding thermoplastic resin polypropylene into a solvent to prepare an electrospinning solution, wherein the concentration of the electrospinning solution is 17%, and placing the electrospinning solution in a syringe of an electrospinning device; S42: loading the polypropylene electrospinning solution into the injection needle tube of the electrospinning device, installing the device on the electrospinning device, and ejecting the polypropylene electrospinning solution from the injection needle tube through the spinneret to form an electrospinning solution jet, with an ejection flow rate of 120 mL / min and a voltage of 20 kV; ejecting titanium dioxide nanoparticles at a constant speed into the polypropylene electrospinning solution jet on the side of the polypropylene electrospinning solution jet, with an ejection speed of the titanium dioxide nanoparticles of 0.3 mg / min, to obtain a polypropylene electrospinning solution jet containing titanium dioxide nanoparticles; S43: The electrospinning liquid jet containing titanium dioxide nanoparticles is sprayed onto a collecting plate to form a polypropylene electrospinning membrane containing titanium dioxide nanoparticles.
[0042] Comparative Example 2 In order to further compare the mechanical properties of the continuous carbon fiber reinforced polypropylene-based composite materials prepared in Examples 4, 5, and 6 with the composite materials prepared by the prior art, 12 pieces of continuous carbon fiber reinforced polypropylene composite prepreg tapes prepared in step S1 of Example 4 were neatly stacked in a mold, the mold was placed in a hot press and closed, the temperature was raised to 240°C, the pressure was maintained at 10 MPa for 10 minutes, the pressure was released and cooled, and then demolded to obtain a continuous carbon fiber reinforced polypropylene composite material with a thickness of about 1.6 mm, which was used as Comparative Example 2 of Examples 4, 5, and 6.
[0043] The mechanical properties comparison of Example 4, Example 5, Example 6 and Comparative Example 2 is shown in Table 2.
[0044] Table 2 product Tensile strength (MPa) Tensile modulus (GPa) Interlaminar shear strength (MPa) Example 4 1400 90 79 Example 5 1470 92 80 Example 6 1500 94 81 Comparative Example 2 1300 89 77 With polypropylene resin as the matrix and continuous carbon fiber as the reinforcement, the continuous carbon fiber reinforced polypropylene resin-based composite material is prepared by adding an electrospinning membrane between the layers of the continuous carbon fiber reinforced polypropylene resin-based composite material prepreg tape, which can improve the mechanical properties of the continuous carbon fiber reinforced resin-based composite material. Compared with the continuous carbon fiber reinforced polypropylene resin-based composite material without the addition of the electrospinning membrane, the interlayer mechanical properties and the comprehensive mechanical properties are improved. Furthermore, the preparation process of the electrospinning membrane of inorganic nanoparticles can promote the effective dispersion of inorganic nanoparticles, and the pores in the electrospinning composite membrane are conducive to the flow and bonding of the interlayer resin, which is conducive to improving the interlayer mechanical properties of the composite material. By adding an electrospinning composite membrane of a high-performance thermoplastic resin containing inorganic nanoparticles between the layers, the dispersion of inorganic nanoparticles (titanium dioxide nanoparticles) can be promoted, and the pores in the electrospinning composite membrane are conducive to the flow and bonding of the interlayer resin, which is conducive to achieving interlayer reinforcement of the continuous carbon fiber reinforced polypropylene resin-based composite material. In particular, the preparation process of the electrospun membrane containing titanium dioxide inorganic nanoparticles in Example 6 can promote the effective dispersion of inorganic nanoparticles, and the pores in the electrospun composite membrane are conducive to the flow and bonding of interlayer resins, which is conducive to improving the interlayer mechanical properties of the composite laminate, and providing a continuous carbon fiber reinforced polypropylene composite material with excellent mechanical properties and a preparation method thereof. By adding a high-performance thermoplastic resin electrospun composite membrane containing inorganic nanoparticles between layers, the dispersion of inorganic nanoparticles (titanium dioxide nanoparticles) between layers can be promoted, and the pores in the electrospun composite membrane are conducive to the flow and bonding of interlayer resins, which is conducive to achieving interlayer reinforcement of continuous carbon fiber reinforced polypropylene-based composite materials.
[0045] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a continuous carbon fiber reinforced resin-based composite material, comprising the following steps: S1: Preparation of continuous carbon fiber reinforced resin matrix composite prepreg tape; S2: adding a thermoplastic resin electrospinning membrane between the layers of the continuous carbon fiber reinforced resin-based composite material prepreg tape obtained in step S1; S3: Compression molding the multi-layer continuous carbon fiber reinforced resin-based composite material prepreg tape with thermoplastic resin electrospinning membrane added between the layers obtained in step S2 to obtain a continuous carbon fiber reinforced resin-based composite material.
2. The preparation method according to claim 1, characterized in that: The preparation method of the continuous carbon fiber reinforced resin prepreg tape includes two methods: solution impregnation method and melt impregnation method.
3. The preparation method according to claim 2, characterized in that: The solution impregnation method comprises the following steps: S11: dissolving the resin in a solvent to form a resin glue solution; S12: After fully impregnating the continuous carbon fiber in the resin glue, drying it to obtain a continuous carbon fiber reinforced resin matrix composite material prepreg tape; The melt impregnation method comprises the following steps: S11: melting the resin matrix at high temperature to form a flowing resin liquid; S12: After the continuous carbon fiber is fully impregnated in the resin flowing liquid, it is cooled to obtain a continuous carbon fiber reinforced resin matrix composite material prepreg tape.
4. The preparation method according to claim 1, characterized in that: The electrospun membrane in step S2 is selected from at least one of an electrospun thermoplastic polyurethane resin film, an electrospun polyvinylidene fluoride film, an electrospun polyaryletherketone film, an electrospun polyarylethersulfone resin film, an electrospun polysulfone film, an electrospun polyethersulfone film, an electrospun polyphenylene sulfone film, an electrospun polyphenylene sulfide film, and an electrospun polyetherimide film.
5. The preparation method according to claim 2 or 3, characterized in that: The resin described in steps S1 and S11 includes at least one of copolymerized aryl ether sulfone resin, polysulfone, polyether sulfone, polyphenylene sulfone, polyphenylene sulfone, polyetherimide, polyaryl ether ketone, and polyamide-imide.
6. The preparation method according to claim 1, characterized in that: The thermoplastic resin electrospinning membrane contains 0.05%-5% by mass of inorganic nanoparticles, and the average particle size of the inorganic nanoparticles is 50-500nm.
7. The preparation method according to claim 6, characterized in that: The inorganic nanoparticles are selected from one or a combination of nano metal oxides, nano metal carbonates, nano metal hydroxides, nano metal sulfates, nano metal nitrates, nano silicon dioxide, nano montmorillonite, and nano kaolin. Preferably, the inorganic nanoparticles are selected from nano calcium carbonate and / or nano montmorillonite.
8. The preparation method according to claim 7, characterized in that: The inorganic nanoparticles are modified calcium carbonate nanoparticles, and the modified calcium carbonate is obtained by treating the surface of calcium carbonate with sodium stearate.
9. The preparation method according to claim 8, characterized in that: The thermal weight loss temperature of the modified calcium carbonate nanoparticles is above 600°C.
10. The preparation method according to any one of claims 6 to 9, characterized in that: The method further includes, between step S1 and step S2: step S4, wherein the thermoplastic resin electrospinning membrane containing inorganic nanoparticles is prepared by the following method: S41: preparing an electrospinning solution, adding a thermoplastic resin and inorganic nanoparticles into a solvent to prepare an electrospinning solution, and uniformly dispersing the electrospinning solution to obtain an electrospinning solution containing inorganic nanoparticles; the concentration of the electrospinning solution is 5%-30%; S42: loading the electrospinning solution containing inorganic nanoparticles into the injection needle of the electrospinning device, installing the device on the electrospinning device, and preparing an electrospinning membrane containing inorganic nanoparticles by an electrospinning process, wherein the voltage is 10-20 kV and the electrospinning solution jet flow rate is 60-200 mL / min; S43: The electrospinning membrane containing inorganic nanoparticles obtained in step S42 is cleaned and then dried.
11. The preparation method according to any one of claims 6 to 9, characterized in that: The method further includes step S4 between step S1 and step S2: the electrospinning membrane containing inorganic nanoparticles is prepared by the following method: S41: preparing an electrospinning solution, adding a thermoplastic resin into a solvent to prepare an electrospinning solution, wherein the concentration of the electrospinning solution is 5%-30%; S42: loading the electrospinning solution into the injection needle tube of the electrospinning device, and ejecting the electrospinning solution from the injection device through the spinneret to form an electrospinning solution jet; ejecting inorganic nanoparticles at a constant speed into the electrospinning solution jet on the side of the electrospinning solution jet to obtain an electrospinning solution jet containing inorganic nanoparticles; S43: The electrospinning liquid jet containing inorganic nanoparticles is sprayed onto a collecting plate to form an electrospinning membrane containing inorganic nanoparticles.
12. The preparation method according to claim 11, characterized in that: The conditions for electrospinning in step S42 are: voltage of 10-20 kV, flow rate of electrospinning solution of 60-200 mL / min, and emission speed of inorganic nanoparticles of 0.1-10 mg / min.
13. The preparation method according to claim 1, characterized in that: The molding temperature in step S3 is 160°C-350°C, the pressure is 5-10MPa, and the hot pressing time is 0.1-1h.
14. A continuous carbon fiber reinforced resin-based composite material obtained by the method according to any one of claims 1 to 13.
Citation Information
Patent Citations
Continuous carbon fiber reinforced phthalazinone structure containing polyarylether nitrile resin-based composite material and preparation method thereof
CN104031376A
Compatilizer for carbon fiber reinforced phthalazinone copolyether sulfone commixed resin-based composite material as well as preparation method and application
CN107513160A
Preparation method and preparation device for carbon fiber-reinforced thermoplastic resin matrix composite material
CN110435185A
Aramid fiber reinforced PPESK base composite material interfacial modifying method
CN1978530A
Cited By
Continuous fiber reinforced composite material for stent-free inflatable gas film and preparation method of continuous fiber reinforced composite material
CN120209366A